THE IMPACT OF TEACHING ENGLISH CULTURE IN EFL CLASSES: CASE STUDY OF MASTER ONE STUDENTS AT THE UNIVERSITY OF LAGHOUAT - Taibi ,Hayat; Seddiki, Mohammed Cherief (University of Ammar Theledji -Laghouat, 2021)
The present study aims at investigating the influence of teaching English culture on Algerian classes as well as identifying teachers' practices and techniques that enhance students' interest in the English culture. As majoring tools two questionnaires conducted at Laghouat University, this study tries to confirm the hypothesies that if students might cooperate and engage in learning cultural content if EFL teachers use cultural information appropriately, Therefore, the first questionnaire was administered for the university teachers of English to find out their teaching strategies. The second questionnaire was directed to master one students. The study reported that foreign language teachers are aware of the importance of culture teaching; they also use different techniques to convey cultural aspects of the target language f or, students showed great interest in incorporating English culture through various techniques to present the target features in their class. In the light of these findings, the present study recommends the integration of the target culture in a foreign language teaching context